Una aplicación de los árboles de expansión mínima y árboles jerárquicos al estudio de la convergencia interregional en dinámica de regímenes - Juan Gabriel Brida; Silvia London; Mara Rojas (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– This paper studies the regional convergence of sub-national states in the case of Mercosur from 1961 to 2005 by using a non-parametric technique of clustering under the concept of egime of performance". In the first section, a review in interregional convergence is shown for the Mercosur case. Then, methodological concepts are introduced: regimens, dynamic of regimens, and clusters evolution. The best positioned Brazilian states show an interregional convergence process in dynamics of regimens towards the richest Argentinean regions and Uruguay; moreover, Paraguay, the North part of Brazil and the historically underdevelopment regions of Argentina are in scenarios of low economic performance, reducing the intra-group distance but showing a divergence process in reference to the highest income group. Results exhibit evidences in favor to convergence clubs of performance. The final discussion deals with the consequences of economic integration on that process.
Keywords: C14; O54; O49; 330; clusters; quantitative methods; environmental performance; economic result; empirical evidence